A NEW GENUS LEIOPHYLLOCERAS (PHYLLOCERATIDA, AMMONOIDEA) FROM THE BERRIASIAN OF THE MOUNTAINOUS CRIMEA - Arkadiev V.V. (My University, 2002)
A new genus, Leiophylloceras (Phylloceratida, Ammonoidea), is described from the Berriasian of the Mountainous Crimea. Shell and sutural ontogeny are discussed.
Keywords: Berriasian; Mesozoic::Cretaceous::Lower::Berriasian; Мезозой::Меловая::Нижний::Берриасский